Refugee migration from Ukraine to other parts of Europe: Challenges to the housing-integration intersection at the city level - Annegret Haase; Harriet Allsopp; Ivette Arroyo; Yvonne Franz; Karlis Laksevics; Valeria Lazarenko; Bahanur Nasya; Ieva Raubisko; Ursula Reeger; Bana Saadeh; Anika Schmidt; Ulrika Stevens (Radical Housing Journal, 2022)
In the context of the massive refugee influx from Ukraine to its European neighbouring states over the last months, this update reflects on the experiences of two international exchanges led by HOUSE-IN: a JPI Urban Europe-funded project that deals with challenges at the housing-integration nexus. The exchanges revealed the impacts of this forced migration at the intersection of housing and integration in several European cities. The update analyses the civic and temporal nature of responses to this refugee movement, which have challenged major assumptions about practices of settling and integration under uncertainties of war, as well as those around access to housing and support.
Keywords: 300; Refugee migration; Ukraine; European cities; housing integration; selective solidarity